2017
DOI: 10.1038/cddis.2017.560
|View full text |Cite|
|
Sign up to set email alerts
|

C-X-C motif chemokine ligand 10 produced by mouse Sertoli cells in response to mumps virus infection induces male germ cell apoptosis

Abstract: Mumps virus (MuV) infection usually results in germ cell degeneration in the testis, which is an etiological factor for male infertility. However, the mechanisms by which MuV infection damages male germ cells remain unclear. The present study showed that C-X-C motif chemokine ligand 10 (CXCL10) is produced by mouse Sertoli cells in response to MuV infection, which induces germ cell apoptosis through the activation of caspase-3. CXC chemokine receptor 3 (CXCR3), a functional receptor of CXCL10, is constitutivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 56 publications
0
25
0
1
Order By: Relevance
“…Exogenous type I IFN induced ISGs and inhibited MuV replication in Leydig cells, macrophages and Sertoli cells (748), demonstrating effective IFN signaling cascade. MuVexposed Sertoli cells secreted high levels of pro-inflammatory cytokines, among which chemokine (C-X-C motif) ligand 10 (CXCL10) triggered germ cell apoptosis (325), suggesting that Sertoli cells might play a key role in MuV-induced inflammation and germ cell damage in the testis (746). Rat testicular macrophages expressed lower levels of TLR4 receptors than peritoneal macrophages (56) as well as low basal expression of TLR-signaling pathway genes (e.g.…”
Section: Rodent Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…Exogenous type I IFN induced ISGs and inhibited MuV replication in Leydig cells, macrophages and Sertoli cells (748), demonstrating effective IFN signaling cascade. MuVexposed Sertoli cells secreted high levels of pro-inflammatory cytokines, among which chemokine (C-X-C motif) ligand 10 (CXCL10) triggered germ cell apoptosis (325), suggesting that Sertoli cells might play a key role in MuV-induced inflammation and germ cell damage in the testis (746). Rat testicular macrophages expressed lower levels of TLR4 receptors than peritoneal macrophages (56) as well as low basal expression of TLR-signaling pathway genes (e.g.…”
Section: Rodent Modelsmentioning
confidence: 99%
“…peritubular cells and extracellular matrix), and degeneration of the germinal epithelium (185). Dysregulation of the testicular cytokinetic microenvironment disrupts both steroidogenesis (271,697,752) and spermatogenesis (53,325,602,681). For instance, during orchitis, infiltrating macrophages and mast cells produce TNF that induces germ cell apoptosis (681), modifies peritubular cell secretions and induces fibrosis (442).…”
Section: Viral Infections and Infertilitymentioning
confidence: 99%
See 1 more Smart Citation
“…A high level of TNF‐α inhibits testosterone production by Leydig cells (12, 13), and early studies showed that MuV infection impairs the function of Leydig cells (14, 15). In addition, TNF‐α production by Sertoli cells in response to MuV infection can induce male germ cell apoptosis (16). Although Sertoli cells are a major target of MuV infection, the effects of MuV infection on the function of these cells remain unclear.…”
mentioning
confidence: 99%
“…Thus, Sertoli cells can activate a strong innate immune response against ZIKV under laboratory conditions and probably represent a major source of cytokines in infected males. It has been shown that TNF-α increases the production of IP-10 in mouse testis and that this chemokine induced germ cell apoptosis in vivo in Mumps virus-infected testicles [ 94 ]. If a similar mechanism occurs in humans, ZIKV infection could have negative impacts on male fertility altering specific stages of the seminiferous epithelial cycle leading to a decline in total sperm count as has been already reported in long term shedders of this virus in semen [ 55 ].…”
Section: Interactions Of Zikv In the Male Reproductive Tractmentioning
confidence: 99%